Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela - Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda; Mejdalani, Gabriel (Zootaxa, 2018)
Two new species of Polana DeLong, 1942 are described and illustrated, P. (Angusana) pilosa sp. nov. from Peru and P. (Declivella) maculosa sp. nov. from Brazil. Polana (Striapona) desela Delong, 1979 is redescribed; the female terminalia of this species are described and illustrated for the first time.